2011
DOI: 10.1242/dmm.002998
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model for monitoring islet cell genesis and developing therapies for diabetes

Abstract: SUMMARYTransient expression of the transcription factor neurogenin-3 marks progenitor cells in the pancreas as they differentiate into islet cells. We developed a transgenic mouse line in which the surrogate markers secreted alkaline phosphatase (SeAP) and enhanced green florescent protein (EGFP) can be used to monitor neurogenin-3 expression, and thus islet cell genesis. In transgenic embryos, cells expressing EGFP lined the pancreatic ducts. SeAP was readily detectable in embryos, in the media of cultured em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Kras LSL-G12D mice (Jackson et al, 2001) and C57BL/6(tetO-Cdkn1b)1Scpr/J mice (Pruitt et al, 2013) were purchased from Jackson Laboratory. Sox9-rtTA transgenic mice were made by recombining the reverse tetracycline transactivator (Clontech; pTet-On) into the Sox9 coding region of a 202kb BAC (RP23-36D5); transgenic mice were generated by the UCSF transgenic core as described (Shimajiri et al, 2011). Transgene expression was induced in pregnant Sox9-rtTA; tetO-Cdkn1b with daily 1 mg intraperitoneal (IP) injections of doxycycline on indicated gestational days.…”
Section: Methodsmentioning
confidence: 99%
“…Kras LSL-G12D mice (Jackson et al, 2001) and C57BL/6(tetO-Cdkn1b)1Scpr/J mice (Pruitt et al, 2013) were purchased from Jackson Laboratory. Sox9-rtTA transgenic mice were made by recombining the reverse tetracycline transactivator (Clontech; pTet-On) into the Sox9 coding region of a 202kb BAC (RP23-36D5); transgenic mice were generated by the UCSF transgenic core as described (Shimajiri et al, 2011). Transgene expression was induced in pregnant Sox9-rtTA; tetO-Cdkn1b with daily 1 mg intraperitoneal (IP) injections of doxycycline on indicated gestational days.…”
Section: Methodsmentioning
confidence: 99%
“…In 50 women vaccinated with HPV16/18 AS04-adjuvanted vaccine, serum SEAP levels correlated with antibody levels measured using ELISA (Kemp et al, 2008). In addition to the measurement of SEAP in blood, it is a useful reporter for in situ histo-enzymatic revelation to correlate the level of its secretion and the number of transduced cells (Shimajiri et al, 2011). …”
Section: Secreted Alkaline Phosphatasementioning
confidence: 99%
“…GDF11 is a key factor in embryonic development, metabolic disorders, and cancers (33,43). Previous studies have shown that restoring systemic GDF11 level reversed age-related cardiac hypertrophy and brain dysfunction (20,23).…”
Section: Introductionmentioning
confidence: 99%